KEPUASAN KERJA, LINGKUNGAN KERJA, BUDAYA ORGANISASI DAN KOMPENSASI TERHADAP LOYALITAS SDM - Haryanto, Haryanto; Sudarwati, Sudarwati; Istiatin, Istiatin (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2025)
This study aims to determine and explain the effect of Job Satisfaction, Work Environment, Organizational Culture and Compensation on HR Loyalty at PT Sadar Group Surakarta.  The population of this study was 51 HR employees at PT Sadar Group Surakarta with a saturated sample. Data collection using a questionnaire. Data analysis techniques using the Multiple Linear Analysis method. The results of the study showed that job satisfaction, work environment, organizational culture and compensation on HR loyalty at PT Sadar Group Surakarta had a positive and significant effect by contributing to loyalty of 66.5% while the remaining 33.5% was explained by other variables not proposed in this study. Suggestions from this study, HR at PT Sadar Group Surakarta can improve work culture in a conducive environment to achieve job satisfaction that can increase loyalty to the company. Keywords: Loyalty, Job Satisfaction, Work Environment, Organizational Culture, Compensation, HR